Comparison of Market Manipulation Regulation Under Australian Law and Indonesian Law - Kairupan, David (Pelita Harapan University, 2002)
Although manipulation is a fundamental concern of the regulation of financial markets, it is not specifically defined in any or the regulatory statutes in Indonesia of abroad, including in Australia. Academic and judicial commentaries have suggested various formulations on market manipulation, although there is no entirely satisfactory definition of the term.2 The essential characteristic of market manipulation are the interference with the free forces of supply and demand in the market for securities, and either the intent to induce other persons to trade in a particular security, or the attempt to force Â the price of a security to an artificial level.3 In essence, the prohibited practices all focus on ways of manipulating the market price of securities by artificial market activity so distorting the securities price that reported price does not reflect the underlying merit of the investment. Manipulative practices may therefore be said to undermine the proper functioning of the securities markets as an appraiser value and is regarded by some reasons as far more significant than insider trading.4 Insider trading tends to move closer to proper levels, while market manipulation distorts the market and makes it less efficient.Â